Association between esophageal varices severity and psychological distress in cirrhotic patients - Mustika, Syifa; Fathoni, Alfan; Sopacua , Andre; Vianty , Liku (PT. DEKA RESEARCH INSTITUTE, 2025)
BACKGROUND: Patients with liver cirrhosis are highly vulnerable to psychological disorders; however, the implications of these mental health issues on the severity of esophageal varices remain unclear. OBJECTIVES: This study aimed to investigate the correlation between the grading of esophageal varices and the occurrence of anxiety and depression in cirrhotic patients experiencing upper gastrointestinal bleeding. METHODS: This study was conducted on inpatients at Dr. Saiful Anwar General Hospital, Malang, who were diagnosed with liver cirrhosis and experienced upper gastrointestinal bleeding over a six-month period using a consecutive sampling method. The grading of esophageal varices from endoscopic data was categorized according to the First Baveno International criteria. Anxiety and depression levels were assessed using the Hospital Anxiety and Depression Scale (HADS). Statistical analysis was performed using the Chi-Square test with a significance level of p-value < 0.05. RESULTS: Out of 53 respondents, 46 had large-grade esophageal varices and 7 had small-grade varices. Based on HADS scores, 38 respondents exhibited symptoms of anxiety, 10 were within the normal range, and 5 exhibited symptoms of depression. A significant moderate correlation was found between the grading of esophageal varices and the presence of anxiety and depression in cirrhotic patients with upper gastrointestinal bleeding (p = 0.001; r = 0.445). CONCLUSION: There is a significant correlation between large-grade esophageal varices and the occurrence of anxiety in cirrhotic patients experiencing upper gastrointestinal bleeding.